A facile method of functional derivatization based on starch acetoacetate. (1st August 2022) - Weng, Tianhang; He, Zejian; Zhang, Zhaohua; Chen, Yulong; Zhou, Mi; Wen, Bianying
Abstract: In the present work, we constructed a methodology to graft starch with special groups, such as alkyl, phenolic, naphthalimide derivatives (ND) and polymer, by a simple reaction under generally mild conditions without catalysts or UV irradiation, based on precursor starch acetoacetate (SAA). The completeness of these reactions has been proved to be ideal. After grafting, the starch derivatives have some common changes, for instance, their solubility is improved in certain solvents. On the other hand, the introduction of different functional groups will also bring some characteristics to the derivatives (e.g. ND brings fluorescence). In addition, part of the derivatives shows excellent machinability, and their hot-pressed samples exhibit great transparency and mechanical strength. Specially, the alkyl grafted starch displays excellent toughness, properties of deformation and self-recovery. In conclusion, this method has good universality and methodological significance, and offers insights into the larger-scale industrial application of starch. Graphical abstract: Based on starch acetoacetate, we constructed a new facile methodology for the synthesis of starch derivatives under mild conditions without catalysts or UV irradiation. The different functional groups introduced endow derivatives with their own characteristics (e.g. fluorescence). Part of the derivatives show great transparency and plasticity, especially, SAA-HA shows excellent toughness, and remarkable deformation and self-healing properties due to the introduction of flexible alkyl chain. Unlabelled Image